Role of miRNA-regulated type H vessel formation in osteoporosis - Zhang, Dailiang; Wang, Yongjing; Zhou, Zunzhen; Wang, Limei; Liu, Chongzhi; Jiang, Yuan (Frontiers in Endocrinology, 2024)
Osteoporosis (OP) is a chronic systemic bone metabolism disease characterized by decreased bone mass, microarchitectural deterioration, and fragility fractures. With the demographic change caused by long lifespans and population aging, OP is a growing health problem. The role of miRNA in the pathogenesis of OP has also attracted widespread attention from scholars in recent years. Type H vessels are unique microvessels of the bone and have become a new focus in the pathogenesis of OP because they play an essential role in osteogenesis-angiogenesis coupling. Previous studies found some miRNAs regulate type H vessel formation through the regulatory factors, including platelet-derived growth factor-BB (PDGF-BB), hypoxia-inducible factor 1α (HIF-1α), vascular endothelial growth factor (VEGF), and so on. These findings help us gain a more in-depth understanding of the relationship among miRNAs, type H vessels, and OP to find a new perspective on treating OP. In the present mini-review, we will introduce the role of type H vessels in the pathogenesis of OP and the regulation of miRNAs on type H vessel formation by affecting regulatory factors to provide some valuable insights for future studies of OP treatment.